Temporal and morphological eruption characteristics of lava flows from the Holocene La Taza monogenetic cone obtained from petrology and LiDAR imagery (Michoacán, Mexico) - Lerner, Geoffrey A. (2024)
The Holocene La Taza andesitic volcano is one of over 1000 volcanic centers located within the Michoacán-Guanajuato Volcanic Field (MGVF) in central-western Mexico. La Taza (~8500–8200 yr BP) represents one possible eruption style within the field, with deposits indicating Strombolian activity followed by a series of lava flows. In our study, we reconstruct the eruption of La Taza through a combination of LiDAR mapping and petrological and geochemical analyses. LiDAR mapping combined with groundtruthing in the field allowed us to differentiate and determine the sequence of the volcano’s lava flows, revealing seven lava flows with a volume of ~0.6 km3. This morphological information was paired with geothermobarometers to estimate lava flow viscosities, mean effusion rates, and emplacement times, showing a likely duration of 1.1–4.3 years. Recreating this eruption contributes to the understanding of potential durations and lava flow rheology of future MGVF eruptions, crucial characteristics for hazard planning and mitigation.